2008
DOI: 10.1002/ijc.23519
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel DNA methylation markers in cervical cancer

Abstract: Testing for DNA methylation has potential in cancer screening. Most previous studies of DNA methylation in cervical cancer used a candidate gene approach. The aim our study was to identify novel genes that are methylated in cervical cancers and to test their potential in clinical applications. We did a differential methylation hybridization using a CpG island (CGI) microarray containing 8640 CGI tags to uncover methylated genes in squamous cell carcinomas (SCC) of the uterine cervix. Pooled DNA from cancer tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
190
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(206 citation statements)
references
References 48 publications
12
190
2
Order By: Relevance
“…18 For analyses of host gene combinations with HPV testing that have included genes PAX1, SOX1, LMX1, NKX6-1 and WTI or CADM1, MAL and miR-124-2, the sensitivity was shown to rise for CIN31. 12,19 In the current study we observed a gain in performance with a linear predictor for the cancer vs. CIN2/3 and CIN2/3 vs. NILM/CIN1 contrasts. By simulating with our data the contrasts that would be of interest in a triage situation to help decide if HPV161 women must be referred for colposcopy implied setting the methylation level of the markers at a threshold that permitted high sensitivity to detect CIN2/3 or cancer.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…18 For analyses of host gene combinations with HPV testing that have included genes PAX1, SOX1, LMX1, NKX6-1 and WTI or CADM1, MAL and miR-124-2, the sensitivity was shown to rise for CIN31. 12,19 In the current study we observed a gain in performance with a linear predictor for the cancer vs. CIN2/3 and CIN2/3 vs. NILM/CIN1 contrasts. By simulating with our data the contrasts that would be of interest in a triage situation to help decide if HPV161 women must be referred for colposcopy implied setting the methylation level of the markers at a threshold that permitted high sensitivity to detect CIN2/3 or cancer.…”
Section: Discussionsupporting
confidence: 54%
“…13 We report herein our analysis of methylation of two HPV16 L1 sites and host CpG sites in genes EPB41L3 and LMX1 that have in recent studies shown promising ability to discriminate among pre-invasive cervical lesion stages. 6,16,[18][19][20][21] We investigated the predictive biomarker ability of these methylation sites across the spectrum of HPV16 positive cervical lesions, from negative for intraepithelial lesions or malignancy (NILM) to cervical cancer.…”
mentioning
confidence: 99%
“…In fact, DNA methylation in host cell genes has been investigated as a potential biomarker for early detection of cervical cancer by extensive screening of premalignant and invasive cervical carcinoma samples (Lai et al, 2008;Whiteside et al, 2008;Fernandez et al, 2009;Ferrari et al, 2009;Wentzensen et al, 2009).…”
Section: Human Papilloma Virusmentioning
confidence: 99%
“…This poor prognosis is mainly attributed to it often being diagnosed at the late clinical stage when surgical treatment and other medical therapies are limited [70] . Serval previous studies show that NKX6.1, a member of the NKX homeodomain-containing family, plays an important roles not only in neuronal tumors [71] , cervical tumors [72][73][74] , lymphoma [75] or islet tumor [76][77] , but also in HCC and may be a predictive risk factor for unfavorable prognosis in patients with HCC [78][79] .…”
Section: Nkx61mentioning
confidence: 99%